Selecting Tree Species with High Carbon Stock Potency from Tropical Upland Forest of Bedugul-Bali, Indonesia - Arief Priyadi; Sutomo Sutomo; I Dewa Putu Darma; Ida Bagus Ketut Arinasa (Journal of Tropical Life Science, 2014)
Vegetation studies to reveal tree diversity and its contribution to carbon stock were conducted in three different sites of upland forest in Bali, Indonesia. The sites were located approximately 60 km north of the Bali Province capital city of Denpasar in an area named Bedugul. Those three sites were Mt. Mangu (forest area east of Beratan lake), forest area west of Buyan lake and forest area south of Tamblingan lake. There were 44, 29, and 21 tree species of 14, 19, 14 families with Shannon Diversity Index (H) of 2.87, 2.64 and 1.69 respectively. Carbon stock average of above ground tree biomass from these sites were 214.2, 693.0 and 749.1 ton.ha-1 respectively. Tree species with top Summed Dominance Ratio (SDR) in each of those sites were Platea latifolia in Mt. Mangu, Planchonella sp. in Buyan, and Tabernaemontana macrocarpa in Tamblingan. Average carbon content of these three species were 493.25, 12,876.26 and 40.35 kg.ha-1 respectively.